Disain Kebutuhan Tulangan Glass Fiber Reinforced Polymer (GFRP) Untuk Elemen Struktur Pada Bangunan Beton Bertulang - Putri, Dhea Triviananda; Kamaldi, Alfian; Ridwan (Dept. of Civil Engineering Universitas Riau, 2023)
Fiber Reinforced Polymer is a combination of two main materials Resin Polymer (plastic) as a binder matrix and Fiber (fiber) as reinforcement. This material has three fibers, namely Carbon, Glass, and Aramid. Glass fiber was used in this study, because it has a greater strain compared to other fibers. This study aims to design reinforced concrete structures using steel reinforcement and GFRP as well as to compare the reinforcement requirements of each reinforced concrete. Calculation of reinforcement for steel reinforced concrete refers to SNI 1726-2019, while for GFRP reinforced concrete it is based on ACI 440 1R-2015. This research begins by collecting data in the form of a design structure drawing of a 6-storey hypothetical building, with a total building height of 23 m. The hypothesis building has the number of spans in the X-axis direction is 5 with a distance between columns of 6 m, while the number of spans in the Y direction is 3 with a distance between columns of 5 m. The column dimensions for all floors are 60 cm x 60 cm, while the beam dimensions are 40 cm x 40 cm. The thickness of the floor and roof slabs is 12 cm and the concrete quality is 30 MPa. For the calculation of structural loading, dead load, live load and earthquake load are used and the design of reinforcement for conventional steel reinforced concrete structures and GFRP is carried out. Steel reinforced concrete structures with GFRP reinforced concrete have differences in the amount and diameter of reinforcement required. For beam elements bearing steel reinforcement, 24 pieces of flexural reinforcement are needed with a diameter of 19 mm, while for beam elements, GFRP reinforcement requires 12 pieces of flexural reinforcement with a diameter of 1 inch to 1,128 inches. For the field area, steel reinforcement beam elements need 12 pieces with a diameter of 19 mm, while for GFRP reinforcing beam elements require 8 pieces of flexural reinforcement with a diameter of 0.875 inch to 1.128 inch. In column elements, steel reinforcement and GFRP reinforcement require the same amount of main reinforcement, which is 32 pieces. However, in terms of diameter, steel reinforcement requires 25 mm diameter reinforcement, while GFRP is 1 inch in diameter.